Household production and consumption impacts of foot and mouth disease at the Uganda-Tanzania border - Kerfua, Susan Diana; Railey, Ashley Flynn; Marsh, Thomas Lloyd (Frontiers in Veterinary Science, 2023)
Introduction Foot-and- mouth disease (FMD) is a highly contagious viral disease that is endemic in East Africa. FMD infection incurs signficant control costs and reduces animal productivity through weight loss, lowered milk yield, and potentially death but how household’s respond to these losses may differentially affect household income and food consumption. Metholodogy To address this, we use unique data from a FMD outbreak to assess how household production and consumption activities change from before to during the outbreak. Data came from a 2018 survey of 254 households in selected Tanzanian wards and subcounties in Uganda. The data includes household recall of before and during an outbreak in the past year on livestock and livestock product sales, milk and beef consumption, as well as related changes in market prices. We apply both difference-in-difference and change in difference regressions with fixed effects to evaluate the impact of FMD on household production and consumption. Results and Discussion We find that households reported the largest reductions in livestock and livestock product sales, followed by reduced milk consumption and animal market prices. The changes in household income from livestock sales appears to be driven by FMD infection within the household herd while changes in market prices of substitute protein sources are primary associated with changes in milk and beef consumption. The role of widespread market price effects across both infected and uninfected households and countries, tends to suggest that stabilizing prices will likely have a large impact on household nutritional security and income generation. We also propose that promoting diversity in market activity may mitigate differing impacts on households in FMD endemic regions.